An Alternative Cuprizone-Induced Demyelination and Remyelination Mouse Model. (August 2017) - Zhen, Wei; Liu, Ailian; Lu, Jiaqi; Zhang, Wandong; Tattersall, David; Wang, Jianfei
The cuprizone model is a well-established and investigated paradigm to study demyelination and remyelination in rodents. Cuprizone is usually administrated by mixing in the powdered or pelleted rodent chow. However, since cuprizone is sensitive to the environment and the consumption of it varies between different animals, the major issue is the discrepancy in demyelination of the animals. This study reports the development of the cuprizone model by gavage administrations in mice. Following testing a series of doses of cuprizone, 400 mg/kg/day was found to be the best dosage to induce dramatic and consistent demyelination after 5 weeks of administration; while remyelination quickly occurred after 9 days of cuprizone withdrawal. The advantage of this alternative model is that the consumption of cuprizone could be well controlled, and the mice were exposed to the same dose of cuprizone. Thus, the variation in demyelination was minimized. This alternative cuprizone dosing regime minimizes the interanimal variability on demyelination and hence provides a consistent model for pharmacological evaluations, in addition to reducing the number of animals used in the experiments.